Applicability of the Fugulin scale: an integrative review (Research, Society and Development, 2023)
Objective: To search for evidence in the literature about the applicability of the Fugulin Scale. Method: Integrative literature review that included original articles from the MEDLINE, LILACS and BDENF databases, in the time frame from 2012 to 2022. The synthesis of the articles was done descriptively according to the type of approach. Results: 1731 articles were identified, of which 5 were included in this review, published in English, all in Brazil. All articles sought to assess the care complexity level of patients in hospitalization units and associate it with the unit's nursing dimension. The application of the scale in a systematized technology allowed access to important results in real time with an impact on time and cost savings. Conclusion: It is concluded that the use of the Fugulin Scale is effective in providing information about the care profile based on the classification of the patients' degree of dependence. The scale applied in a technological way is related to the optimization of time, decision-making process and impact on costs and energy.